Ecological Balance of the Life Cycle of the Battery Electric Vehicles - Anisits , Ferenc (International Journal of Engineering and Management Sciences, 2019)
The economic and ecological assessment of propulsions for mobil applications is based on the analysis oft he entire chain of energy transformation. In this regard, the ecological assessment oft he automobile is complemented by emissions created during its production and ist recycling. The following paper aims at promoting the understandig oft he underlying subject matter and to make the reader aware of relevant aspects that must be looked for in similar assessments. Understanding the discussed contex makes it possible to objectively asses the contribution of BEVs (battery electric vehicles) to the enviroment. The assessment provides hints thet help discover problem areas and assist in deducting goals and measures fort he strategy of emobility.